2017
DOI: 10.1002/jrs.5254
|View full text |Cite
|
Sign up to set email alerts
|

Aligned diphenylalanine nanotube–silver nanoparticle templates for high‐sensitivity surface‐enhanced Raman scattering

Abstract: Self‐assembly offers potential routes for large‐scale, rapid, and cost‐effective surface‐enhanced Raman scattering (SERS) substrate designs. Here, a highly sensitive SERS template is reported, which utilizes aligned diphenylalanine nanotubes to form a dense packing arrangement of plasmon‐active silver nanoparticles. The template is stable under high laser illumination with a power density of ~6.25 MW/cm2 in comparison to only silver nanoparticles and enables picomolar and femtomolar probe molecule concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 50 publications
3
39
0
1
Order By: Relevance
“…SERS measurements were performed using a bespoke Raman system that consisted of an inverted optical microscope (IX71, Olympus), a monochromatic laser (HeNe, ThorLabs) with beam splitter and long pass filter (RazorEdge, Semrock), a spectrograph (SP-2300i, Princeton Instruments), and a CCD camera (IXON, Andor) 49 , 50 . To focus the laser (532 nm wavelength, 3.56 mW incident power), a 50x objective was used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SERS measurements were performed using a bespoke Raman system that consisted of an inverted optical microscope (IX71, Olympus), a monochromatic laser (HeNe, ThorLabs) with beam splitter and long pass filter (RazorEdge, Semrock), a spectrograph (SP-2300i, Princeton Instruments), and a CCD camera (IXON, Andor) 49 , 50 . To focus the laser (532 nm wavelength, 3.56 mW incident power), a 50x objective was used.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the fact that many substrate designs have been developed to increase Raman intensity, there are very few studies in the literature that have used FF-PNTs as a template to support SERS active substrates 49 51 . It has been previously reported that aligned FF-PNT templates formed with plasmon-active Ag NPs enabled SERS detection of molecules 49 , 50 . Here, we report UV-enhanced SERS from Ag NPs on aligned, semiconducting FF-PNTs.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10] Peptide-metal NP composites, in particular, have been used for drug delivery and electrochemical biosensing applications, [11][12][13] and more recently, in surface-enhanced Raman spectroscopy (SERS)-based sensing applications using FF-nanotube-metal NP composites. [14][15][16] Although nanoparticles and organic-nanoparticle composites that may facilitate cellular and biomolecular sensing applications have been assembled through bio-templating and self-assembly routes, 14,16,[25][26][27][28][29][30][31][17][18][19][20][21][22][23][24] few of these have been used for SERS, 14,[16][17][18][19]25,28,29,31 and none are based on Fmoc-FF.…”
Section: Introductionmentioning
confidence: 99%
“…Almohammed et al studied aligned diphenylalanine nanotube‐silver nanoparticle templates for high‐sensitivity SERS. A highly sensitive SERS template is reported, which utilizes aligned diphenylalanine nanotubes to form a dense packing arrangement of plasmon‐active silver nanoparticles . Azhniuk et al used Raman band intensities to study chemical composition of glass‐embedded quaternary CdS 1‐x‐y Se x Te y nanocrystals.…”
Section: Nannomaterialsmentioning
confidence: 99%
“…A highly sensitive SERS template is reported, which utilizes aligned diphenylalanine nanotubes to form a dense packing arrangement of plasmonactive silver nanoparticles. [90] Azhniuk et al used Raman band intensities to study chemical composition of glassembedded quaternary CdS 1-x-y Se x Te y nanocrystals. The authors attempted to quantify the nanocrystal chemical composition based on the corresponding LO phonon band intensity ratios by taking into account the effect of polaron constants.…”
Section: Carbon Nanotubes Carbon Materials Graphene Layered Solimentioning
confidence: 99%